A Study on Social Responsibility and Sustainable Development of India: With Special Reference to Selected SDGS - Dr. Meghna Jain (Journal of Social Responsibility, Tourism and Hospitality, 2023)
A systematic review has been conducted in this research and has explained various initiatives taken by India towards sustainable development initiatives. There are different articles based on sustainable development and many of them have been referred in this study. The published articles have been considered for review. The number of studies based on SDGs are limited and only a few of them have been discussed in the previous studies. There are different SDGs which have been covered in this study. A detailed information about the SDGs have been discussed further in this article. In this article, literature based on SDGs has been combined indicating the activities which were conducted in India during last few decades and for arranging them based on SDGs. This particular article aimed to evaluate progress which India has made during last few years and also aimed to evaluate progress in our country associated with sustainable development during last few years.